If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 11 = 15x + -4 + -14x Combine like terms: -2 + 11 = 9 9 = 15x + -4 + -14x Reorder the terms: 9 = -4 + 15x + -14x Combine like terms: 15x + -14x = 1x 9 = -4 + 1x Solving 9 = -4 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9 + -1x = -4 + 1x + -1x Combine like terms: 1x + -1x = 0 9 + -1x = -4 + 0 9 + -1x = -4 Add '-9' to each side of the equation. 9 + -9 + -1x = -4 + -9 Combine like terms: 9 + -9 = 0 0 + -1x = -4 + -9 -1x = -4 + -9 Combine like terms: -4 + -9 = -13 -1x = -13 Divide each side by '-1'. x = 13 Simplifying x = 13
| x+3(x-4)=-72 | | (x+10)*(x+10)=9 | | -8-2x=-7-7x | | -4-6=12-10x | | -99=-3(-7x-2) | | 6x+4x=200 | | -6.5+x=12.25 | | 6g-6-3-6g= | | -3y-12=5y+44 | | 12(n+7)=4(21+3n) | | y=3x^2(x^2) | | [4x-20]+5=12 | | 7x-(2+4x)= | | .3x-.06x=1.25 | | 4p+4q=40 | | -280=7(-5x-5) | | 271-5x=40x+21 | | 5n-4(5n-5)=50 | | 4(2x-7)=8-x | | 2=-(5x-7) | | 252=6(5x+7) | | 5a-(4)=21 | | 7(y+8)=9y+56 | | 5x+36=14x-45 | | 32=-81(1-5x) | | 5a-4=21 | | [2y+1]=-7 | | 3(4r-6)=78 | | [x+2]=7 | | -3(-m-2)=-18 | | x-14=-5-29 | | 25x+5(x-5)+10(x-9)= |